STUDENTS ASSESSMENT IN THE FACULTY OF MEDICINE UNIVERSITY OF GEZIRA - Mirghani, Omer Ahmed; Mohamed, Mohamed El Sanousi (Gezira Journal of Health Sciences, 2006)
This is a description of (i) 15 methods of evaluation used in the assessment of students (ii) criteria used for selection of those methods (objectives domains, validity, reliability, practicability objectivity)(iii) the absolute criteria tests based on a pre-set MPL (iv) methods of evaluation of the evaluation methods (discriminating index and difficulty index (v) methods of evaluation used in each course in FMUG.  The methods of evaluation used are (I) MCQs (2) essay (3) clinical/oral (4) OSCE (5) practical exam (6) log book (7) write-up (8) attendance (9) performance (10) students product report (11) family problem (12) reports from rural hospital doctors (13) supervisory checklist, (14) peer evaluation, (15) community feedback